A Model for Seed Transmission of a Plant Virus: Genetic and Structural Analyses of Pea Embryo Invasion by Pea Seed-Borne Mosaic Virus. - Wang, D. (1994)
Pea seed-borne mosaic virus (PSbMV), a seed-transmitted virus in pea and other legumes, invades pea embryos early in development. This process is controlled by maternal genes and, in a cultivar that shows no seed transmission, is prevented through the action of multiple host genes segregating as quantitative trait loci. These genes control the ability of PSbMV to spread into and/or multiply in the nonvascular testa tissues, thereby preventing the virus from crossing the boundary between the maternal and progeny tissues. Immunocytochemical and in situ hybridization studies suggested that the virus uses the embryonic suspensor as the route for the direct invasion of the embryo. The programmed degeneration of the suspensor during embryo development may provide a transient window for embryo invasion by the virus and could explain the inverse relationship between the age of the mother plant for virus infection and the extent of virus seed transmission.